The Effect Of Emotional Intelligence And Organizational Commitments On Legal Behavior Organizations (Ocb) With Internal Locus Control As A Mediation Variable - _, Nurhikmah; Remmang, Hasanuddin (Postgraduate Bosowa University Publishing, 2018)
This study aims to analyze the influence of emotional intelligence, organizational commitment on Organi-zational Citizenship Behavior (OCB) with Internal Locus of Control as a mediation variable at PT. Mandala Multifinance. The method used in this research is quantitative analysis. The population in this study is 165 employees. Sampling using Slovin formula and obtained as many as 62 respondents. Data collection techniques by distributing questionnaires and data analysis techniques used are Structural Equation Model (SEM) based on Partial Least Square (PLS) 3.0. The results showed that Internal Locus of Control had no influence of mediation between emotional intelligence on Organizational Citizenship Behavior (OCB), the result of analysis with p-values 0,29 did not significantly influence with level of significance 0,05. But the Internal Locus of Control mediates the effect of organizational commitment on Organizational Citizenship Behavior (OCB) based on an analysis with p-values 0.00 with a significancce of 0.05.